Recovery-focused care planning and coordination in England and Wales: a cross-national mixed methods comparative case study - Simpson, Alan (BMC Psychiatry, 2016)
BACKGROUND: In the UK, concerns about safety and fragmented community mental health care led to the development of the care programme approach in England and care and treatment planning in Wales. These systems require service users to have a care coordinator, written care plan and regular reviews of their care. Processes are required to be collaborative, recovery-focused and personalised but have rarely been researched. We aimed to obtain the views and experiences of stakeholders involved in community mental health care and identify factors that facilitate or act as barriers to personalised, collaborative, recovery-focused care. METHODS: We conducted a cross-national comparative study employing a concurrent transformative mixed-methods approach with embedded case studies across six service provider sites in England and Wales. The study included a survey of views on recovery, empowerment and therapeutic relationships in service users (n = 448) and recovery in care coordinators (n = 201); embedded case studies involving interviews with service providers, service users and carers (n = 117) and a review of care plans (n = 33). Quantitative and qualitative data were analysed within and across sites using inferential statistics, correlations and framework method. RESULTS: Significant differences were found across sites for scores on therapeutic relationships. Variation within sites and participant groups was reported in experiences of care planning and understandings of recovery and personalisation. Care plans were described as administratively burdensome and were rarely consulted. Carers reported varying levels of involvement. Risk assessments were central to clinical concerns but were rarely discussed with service users. Service users valued therapeutic relationships with care coordinators and others, and saw these as central to recovery. CONCLUSIONS: Administrative elements of care coordination reduce opportunities for recovery-focused and personalised work. There were few common understandings of recovery which may limit shared goals. Conversations on risk appeared to be neglected and assessments kept from service users. A reluctance to engage in dialogue about risk management may work against opportunities for positive risk-taking as part of recovery-focused work. Research to investigate innovative approaches to maximise staff contact time with service users and carers, shared decision-making in risk assessments, and training designed to enable personalised, recovery-focused care coordination is indicated. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-016-0858-x) contains supplementary material, which is available to authorized users.